New code structure for spectral amplitude coding OCDMA system - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid; R. Badlishah, Ahmad (The institute of Electronics, Information and Communication Engineers (IEICE), 2009)
Link to publisher's homepage at http://www.jstage.jst.go.jp